THE ILLUSTRATED TRAVELOGUE OF GNEDICH: ISTANBUL IN 1894 THROUGH THE EYES OF A RUSSIAN ART HISTORIAN - KÖK, ELİF (EGE UNIV, 2021)
Travelogues presenting the observations of European travelers about Istanbul in the 19th century are well known and many of them have been widely studied. Among many travelogues about Istanbul in the 19th century, this paper focuses on the observations of a less known but distinctive personality, a Russian art historian. Known as the author of the first art history book in Russia, Petr Petrovich Gnedich was also a renowned literary figure and translator of his time. He was an intellectual who knew many aspects of European arts and culture; it is understood that he was also closely interested in the travel literature of the period. However, his encounter with the Eastern world and Istanbul was much later than his recognition of the West. Actually, Istanbul was not only a favorite destination of Western travelers; Russian pilgrims have also been visiting the city for centuries and recording their observations. But unlike these religiously focused travels, Gnedich's impressions are towards a holistic understanding of the city. Besides, his evaluation of the city in terms of art and architectural history differs him from many other travelers. However, he still has an exclusionary attitude towards Ottoman art and architecture, praising the lost glory of Byzantine art. As an intellectual reflecting the common attitudes of his time, his impressions of Istanbul's architectural heritage are interesting and sometimes surprising. Throughout his book, it is repeated in various contexts that he considers no epoch of Ottoman architecture as advanced as Byzantine or European architecture; it can be said that he did not consider the Ottoman monuments unique in many aspects, and his comments in this context were also reflected in his art history book. These notes give clues about the approaches of the Russian intellectuals to the Ottoman world, which seemed to be strongly influenced by European thought and literature at that time. All in all, Gnedich's travel notes provide a vivid panorama of Istanbul in the last years of the 19th century. The book conveys the daily life practices as well as the architectural features of the city with clarity, fluency, and from the author's perspective. He observed not only sacred buildings and touristic areas, but also cemeteries, back streets and theaters, and recorded them as both vivid literary narratives and visuals. Numerous engravings accompanying the texts also contribute to the creation of this lively image of Istanbul. The timing of his travel also makes this testimony important because it happened just after the devastating earthquake in 1894. Traces of this great destruction can also be seen in some engravings in the book. Witnessing a remarkable period of Istanbul, Gnedich's book, which has not been evaluated before, is an important historical document that reflects the physical structure of the city and the perception of Istanbul by a Russian art historian.
Keywords: Istanbul; 19th century; travel writing; Russian travelogues; Ottoman